Legal Education-Informed Cognitive Behavioural Therapy (LiCBT) to improve victims’ confidence in the Nigerian police: a single-arm mixed method feasibility intervention study - Tarela Juliet Ike; Dung Ezekiel Jidong; Evangelyn Ebi Ayobi (Cogent Social Sciences)
Police accountability is essential for affected victims and public trust-building, yet there are limited interventions addressing this issue. A mixed method design was adopted to examine the feasibility, appropriateness, and acceptability of a Legal Education-informed Cognitive Behavioural Therapy (LiCBT) for improving victims’ confidence using 24 participants from Delta-State, Nigeria. Participants were assessed using the Legal-Consciousness-Questionnaire, Legal Awareness of Complaint Channel Scale and the PHQ-9. Wilcoxon Signed-Rank test was used to analyse quantitative data, while the qualitative analyses involved thematic-analysis from a social identity theoretical lens. The study recorded retention rates of 96% in the 12-sessions and 100% in the baseline, end-of-intervention and 3-months follow-ups. Participants showed increased knowledge of their legal rights (LCQ) from baseline (Md = 1.00) to end of intervention (Md = 4.00) with z = −4.427, and at 3-months follow-up, z = −4.423. Findings also showed reduced depression from baseline (Md = 4.00) to end of intervention (Md = 1.00) with z = −4.061 and at 3 months (Md = 1.00) with z = −4.142. LiCBT is acceptable and feasible for improving legal knowledge, reducing depression, including improving positive attitudes towards the police. A fully powered randomised control trial is recommended to test its effectiveness.